2012
DOI: 10.1073/pnas.1216913110
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular superoxide dismutase is important for hippocampal neurogenesis and preservation of cognitive functions after irradiation

Abstract: Cranial irradiation is widely used in cancer therapy, but it often causes cognitive defects in cancer survivors. Oxidative stress is considered a major cause of tissue injury from irradiation. However, in an earlier study mice deficient in the antioxidant enzyme extracellular superoxide dismutase (EC-SOD KO) showed reduced sensitivity to radiation-induced defects in hippocampal functions. To further dissect the role of EC-SOD in neurogenesis and in response to irradiation, we generated a bigenic EC-SOD mouse m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 38 publications
6
60
0
Order By: Relevance
“…A recent study has reported irradiation to reduce dendritic spine density, an effect that could be ameliorated by manipulating the oxidative microenvironment (36). The capability of irradiation to induce an acute and persistent oxidative stress in vitro and in vivo (11) suggest changes in the microenvironmental redox state may play a role in the regulation of spine density and morphology.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has reported irradiation to reduce dendritic spine density, an effect that could be ameliorated by manipulating the oxidative microenvironment (36). The capability of irradiation to induce an acute and persistent oxidative stress in vitro and in vivo (11) suggest changes in the microenvironmental redox state may play a role in the regulation of spine density and morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the deficiency of different SOD family members (e.g., CuZnSOD, MnSOD and EC-SOD) also varies the effects of cranial irradiation [8,27,29,46]. Future studies are yet required to examine these effects at cellular levels to understand the direct contribution of these SODs to adult neurogenesis upon oxidative stress; moreover, specific pharmacological tools against different SODs will provide additional evidences for their different functions in NSCs/NPCs [10].…”
Section: Ros Regulation Over the Adult Neurogenesismentioning
confidence: 96%
“…On the other hand, boosting SOD function or overexpression of SOD could act as Bneuroprotection^upon cranial irradiation, and preserve the cognition function dependent on hippocampus [46]. Interestingly, the SOD overexpression antagonizes the ageing induced spatial memory decreases, but did not prevent the ageing-related decline in neurogenesis in aged mice [11].…”
Section: Ros Regulation Over the Adult Neurogenesismentioning
confidence: 97%
“…Antioxidant reduces the deleterious activity of oxidative stress and potentially delays the development of neurodegenerative disease, the study of antioxidant enzyme in neurogenesis is very important for prevention of the development of neurodegenerative disease. The recent finding showed that when examined at 3-4 months of age, genetic deficiency of extracellular superoxide dismutase (SOD) was associated with a significant suppression of baseline neurogenesis and impaired hippocampal-dependent cognitive functions (Zou et al, 2012). Other study also demonstrated that lack of extracellular SOD in the microenvironment impacts radiation-induced changes in transgenic mice compared with non-tg mice.…”
Section: Introductionmentioning
confidence: 81%